(untitled) (Marketing Journal, 2026)
The role and importance of production resources in ensuring the effectiveness of enterprisesʼ activities is extremely large. The article studies the organization of management in textile enterprises in order to establish effective use of production resourc es and their effective use in stimulating demand in the domestic market, and develops proposals and recommendations.